2013
DOI: 10.1186/1471-2474-14-328
|View full text |Cite
|
Sign up to set email alerts
|

Strength gain through eccentric isotonic training without changes in clinical signs or blood markers

Abstract: BackgroundLocalized exercises are widely used in rehabilitation processes. The predominant options are exercises with an emphasis on either concentric or eccentric contractions. Eccentric exercises promote greater strength gains compared to classical concentric stimuli, but can cause muscle damage. The aim of present study was to compare strength training composed of 10 sessions with progressive loads between groups with a predominance of concentric versus eccentric contraction through an analysis of isotonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
2
1
0
Order By: Relevance
“…The results from the current study show that systemic levels of TNFα are not significantly altered by an 8-week RT program. This is also in somewhat of agreement with the study of Alves et al (2013) whom reported that following 10 RT sessions over 3 weeks, there were no significant changes in circulating TNFα 24–96 h post the final RT session. The current study is slightly in contrast with that of Paoli et al (2015).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results from the current study show that systemic levels of TNFα are not significantly altered by an 8-week RT program. This is also in somewhat of agreement with the study of Alves et al (2013) whom reported that following 10 RT sessions over 3 weeks, there were no significant changes in circulating TNFα 24–96 h post the final RT session. The current study is slightly in contrast with that of Paoli et al (2015).…”
Section: Discussionsupporting
confidence: 91%
“…In a study by Townsend et al (2013) also investigating the acute response to RT, the authors showed that in resistance-trained men, circulating TNFα was significantly increased immediately post-RT compared to pre-RT. However, TNFα levels had returned to baseline within 30 min post-RT, remaining as such for a further 24 and 48 h. This is in somewhat of agreement with the study of Alves et al (2013) who demonstrated that following either eccentric or concentric RT only, there were no acute increases in TNFα post-RT (24–96 h). Furthermore, this study also showed that following 10 RT sessions over 3 weeks, there were no significant changes in circulating TNFα 24–96 h post the final RT session.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation